Interaction of Human Complement Factor H Variants Tyr402 and His402 with Leptospira spp. - Silva, Aldacilene S.; Castiblanco Valencia, Mónica M.; Cianciarullo, Aurora M.; Vasconcellos, Silvio A.; Barbosa, Angela S.; Isaac, Lourdes (Frontiers in Immunology, 2011)
Leptospirosis is a zoonosis caused by pathogenic bacteria from the genus Leptospira. The disease represents a serious public health problem in underdeveloped tropical countries. Leptospires infect hosts through small abrasions in the skin or mucous membranes and they rapidly disseminate to target organs. The capacity of some pathogenic leptospiral strains to acquire the negative complement regulators Factor H (FH) and C4b Binding Protein (C4BP) correlates with their ability to survive in human serum. In this study we assessed the functional consequences of the AMD-associated polymorphism FH His402 or FH Tyr402 on FH-Leptospira interactions. In binding assays using sub-saturating amounts of FH, the FH Tyr402 variant interacted with all the strains tested more strongly than the FH His402 variant. At higher concentrations, differences tended to disappear. We then compared cofactor activities displayed by FH His402 and FH Tyr402 bound to the surface of L. interrogans. Both variants exhibit similar activity as cofactors for Factor I-mediated cleavage of C3b, thus indicating that they do not differ in their capacity to regulate the complement cascade.